The Actual Suspension of the Constitution of the Republic of Iraq for the Year (2005) and its Relationship to the Principle of Legality - Mansour, Hiba (Journal of Legal Sciences, 2023)
The constitution is considered the supreme law in the state, as it clarifies the form of the state and the existing system of government in it, and defines its general authorities and their relationship to each other on the one hand, and their relationship to individuals on the other hand, and this is what the Iraqi constitutional legislator stipulated according to the constitution (2005). However, one of the public authorities in the state may sometimes resort to stopping the implementation of some provisions of the constitution without relying on a constitutional text that gives it the authority to do this work, and this is what has been termed the actual suspension of the constitution. What complicates the matter in Iraq is the political crisis in the Iraqi constitution for the year (2005) /subject of study/ following the legislative elections for the House of Representatives. Especially what happened after the parliament elections in 2021 in terms of conflicts between the political blocs and parties, which in turn led to the disruption of the oversight work of the parliament on the performance of the executive authority. In addition to obstructing the exercise of the legislative role of the House of Representatives, especially with regard to approving the Federal General Budget Law, not to mention the actual obstruction of the approval of the draft law of the Federal Supreme Court, which is considered the final authority for the rest of the authorities. For all of this, we chose this topic with the aim of: Studying - the actual suspension of the Constitution of the Republic of Iraq for the year (2005) - in its general theoretical and conceptual framework, an independent scientific study, By extrapolating the Iraqi political reality and comparing it with the provisions of the constitution related to the three authorities (the legislative authority, the executive authority, and the judicial authority), and developing solutions that guarantee addressing the bitter political reality according to the principle of legitimacy. In our study of this topic, we followed the descriptive and analytical methods to analyse the texts of the Constitution of the Republic of Iraq for the year 2005 related to the subject of the study. We divided the subject of the study accordingly into two sections as follows: The first section came under the title of "Disabling the Constitution" and its differentiation from other related concepts and justifications. The second section was titled "The Actual Disabling of Public Authorities According to the Constitution of the Republic of Iraq for the year 2005 and its Relation to the Principle of Legitimacy." We concluded the study with a conclusion that included a sentence of results and recommendations. One of the most important results we reached is that : The relationship between the actual disabling of the constitution and legitimacy according to the Iraqi Constitution for the year 2005 is manifested in the failure of rulers to commit to the principles contained in the constitution and intentionally neglect them towards the principle of the constitution’s supremacy and the principle of separation of powers, which are effective guarantees for the principle of legitimacy. As for the most important proposals and recommendations, • We suggest that the Iraqi constitutional legislator addresses the flaws in the texts of the Constitution of the Republic of Iraq for the year 2005 by completing the constitutional amendments provided for in Article (142) of the Constitution and adding a text that includes the adoption of the principle of citizenship in the heart of the constitutional document and its application as the sturdy fence to safeguard the constitution from violations and achieve stability in the system of government and its institutions. • To achieve constitutional justice, guarantee individual rights and freedoms, and legitimise the decisions of the Federal Supreme Court, we recommend that the Iraqi legislator expedite the enactment of the Federal Supreme Court Law to address the political crisis and overcome the impasse of the disabling.